Energy Efficient Spectrum Management in Cognitive Radio Sensor Networks - Kaschel-Carcamo, H; Toledo-De la Garza, K (Institute of Electrical and Electronics Engineers Inc., 2017)
Cognitive Radio has been proposed as a solution to the spectrum underutilization problem in Wireless Sensor Networks. This paper describes most used cooperative and non-cooperative sensing techniques in Cognitive Radio Sensor Networks. Energy detection is an optimal method when no prior information about primary signal is available. However, most of the contribution focus on the cooperative sensing in order to addressed the hidden terminal problem. In this regard, a detailed taxonomy about energy efficient spectrum management is the main contribution of this paper. In addition, challenges and future works of this research field have been described. Optimization problems based on primary user predictions and detection performance are a tentative solution to energy efficient spectrum management in Cognitive Radio Sensor Networks.